Evaluation of Retail Meat as a Source of ESBL Escherichia coli in Tamaulipas, Mexico - Ana Verónica Martínez-Vázquez; Antonio Mandujano; Eduardo Cruz-Gonzalez; Abraham Guerrero; Jose Vazquez; Wendy Lizeth Cruz-Pulido; Gildardo Rivera; Virgilio Bocanegra-García (MDPI AG, 2022)
In recent decades, the appearance of a group of strains resistant to most β-lactam antibiotics, called extended-spectrum β-lactamases (ESBLs), has greatly impacted the public health sector. The present work aimed to identify the prevalence of ESBL-producing Escherichia coli strains in retail meat from northeast Tamaulipas. A total of 228 meat samples were obtained from 76 different stores. A prevalence of E. coli ESBL of 6.5% (15/228) was detected. All (15/15) of the ESBL strains were multiresistant. Altogether, 40% (6/15) of the strains showed the presence of class 1 integrons. The isolates identified with blaCTX-M (20%) also showed co-resistance with the tet (A and B), str (A and B), and sul (2 and 3) genes. A total of 20% of the strains belonged to the B2 and D phylogroups, which are considered pathogenic groups. None of the ESBL-positive strains contained any of the virulence gene factors tested. The presence of ESBL-producing E. coli strains in meat indicates a potential risk to the consumer. Although most of these strains were classified as commensals, they were found to serve as reservoirs of multiresistance to antimicrobials and, therefore, are potential routes of dispersion of this resistance to other bacteria.